Apakah Romantic Breakup Berperan terhadap Perilaku Impulsive Buying? : Studi Korelasional pada Mahasiswa - Azmy Nurulhusaini Itsnan Achmad; Megawati Batubara (Jurnal Paedagogy, 2023)
This study aims to identify the relationship and role of romantic breakups on impulsive buying in college students. This study used a non-experimental correlational method with a quantitative approach through regression and descriptive statistical analysis. The sampling technique used in this study was non-probability sampling with a saturation sampling method. The subjects consisted of 62 students of the Faculty of Psychology at a University in Bandung who had experienced a romantic breakup. Data was collected through an online questionnaire containing the Breakup Distress Scale (BDS) and Impulse Buying Tendency Scale (IBTS) measuring instruments using the help of Google Forms. Data analysis techniques used Pearson's Correlation test and regression test. The results of this research showed that there was no significant role of distress due to a romantic breakup in impulsive buying (r2 = 0.004; p = 0.605).